Analysis of the inequalities of oral cancer burden from a global perspective - LUO Lisha; LUAN Hanghang; WU Lan; HUANG Jiao (Yixue xinzhi zazhi)
Objective To investigate the inequalities of oral cancer burden caused by socioeconomic development differences in worldwide from 1990 to 2019, to provide scientific evidence for the development of effective prevention and control policies.Methods The burden of disease data for this study was derived from the 2019 Global Burden of Disease Study, and the human development index (HDI) were from the Human Development Report 2020. Linear regression analysis was used to assess the correlation between age-standardized disability-adjusted life year (DALY) rates and HDI. The slope index of inequality (SII) and concentration index (CI) were used to evaluate the inequalities and their trends of oral cancer burden from 1990 to 2019.Results A total of 189 countries and territories were included in this study. The DALY rate for oral cancer in 2019 was 46.61[IQR(30.70, 64.97)]. The linear regression results showed a significant negative correlation between DALY rate and HDI level (ρ=-0.06, P